Strategi Pengelolaan Pajak Daerah Dalam Upaya Peningkatan PAD di Kota Serang - Pancawati Sugiharti Multiningsih; Arenawati Arenawati; Rina Yulianti (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2021)
This study focuses on the analysis of local tax management strategies in an effort to increase PAD in Serang City. The theory uses SWOT analysis according to Hunger (2017: 23) which includes factors of strength (strength), weakness (weakness), opportunities (opportunities) and threats (threats). The research method uses case studies. The research approach uses a qualitative approach with a qualitative descriptive design. Research informants from BPKAD elements of Serang City, secretary of Commission III DPRD Serang City for Finance and Regional Assets, and hotel, restaurant and entertainment companies. Data analysis using data analysis techniques Miles and Huberman. The results of the study show that the SO (Strenghs to Opportunity) strategy is by adding local tax services that are carried out online, and adding new local taxpayers through data collection activities or direct surveys to the location of business activities engaged in hotels, restaurants and entertainment, WO strategy (Weakness to Opportunity) by adding field officers to carry out data collection and survey activities for business actors, especially small and medium-sized businesses that have not been registered as local taxpayers, ST Strategy (Strenghs to Threats) by utilizing the Serang City BPKAD website to periodic reporting of local taxes to the public, the WT (Weakness to Threats) strategy by means of publicity of local tax information can utilize print media and electronic media.